Management of the Middle Vault - Pruthi, Asheema; Dobratz, Eric; Dougherty, William (Facial Plastic Surgery, 2023)
Early reductive rhinoplasty techniques focused on hump reduction and tip plasty with minimal focus on treating or preserving the integrity and width of the middle vault. With time, rhinoplasty surgeons noted the aesthetic and functional complications of the deformities that may occur in the middle vault with reduction techniques and developed methods to treat and also avoid these complications. Thus, the importance of protecting the integrity of the middle third of the nose has been increasingly emphasized over the years. Primary deformities of the middle vault that result in nasal obstruction require attention of the rhinoplasty surgeon, as well as preservation of support structures of the middle vault and internal nasal valve to minimize secondary deformities and functional compromise after rhinoplasty surgery.
Keywords: rhinoplasty; middle vault; internal nasal valve; spreader graft; endonasal spreader graft